Factors Associated with Self-Reported Arthritis 7 to 24 Years after a Traumatic Brain Injury. Issue 1 (February 2014) - Ocampo-Chan, Sharon; Badley, Elizabeth; Dawson, Deirdre R.; Ratcliff, Graham; Colantonio, Angela
The purpose of this study was to profile characteristics of people with traumatic brain injury (TBI) who self-reported arthritis 7 to 24 yr. post-injury. Pre- and post-injury socio-demographic factors, injury-related factors, and post-injury standardized assessments measuring health, activity, and participation outcomes were assessed in a retrospective cohort study of 274 participants. The group self-reporting arthritis had significantly more sleep disturbances, poorer overall health, lower mental health and physical function, and decreased productivity. Also, they were older and reported a shorter length of loss of consciousness from TBI. These results suggest that musculoskeletal complaints from long-term survivors of TBI should be addressed in post-acute care and could guide future research on arthritis in the TBI population.